2007
DOI: 10.1139/a07-002
|View full text |Cite
|
Sign up to set email alerts
|

Implications of climate warming for Boreal Shield lakes: a review and synthesis

Abstract: Climate change is a reality. A warming climate will have large effects on lakes of the Boreal Shield. Our ability to forecast these effects, however, is hampered by a very incomplete understanding of the actual interactions between weather and many aspects of lake ecosystems. Climate change will affect lakes in very complex ways. Changing weather conditions will have direct effects on thermal habitats; however, there will also be very important indirect effects on lake ecosystems through influences on watershe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 107 publications
3
94
0
Order By: Relevance
“…The stratification process creates a potential for temperature differentials between deeper offshore and shallower near-shore subhabitats within a lake, as temperatures remain relatively constant in deep habitats, whereas shallower near-shore temperatures are strongly influenced by air temperatures (26). Monitoring in the boreal region (27,28) has shown that rising air temperature warms surface waters, accelerates the stratification process, and extends the duration of stratification; thus, air temperature is a primary determinant of lake thermal heterogeneity.…”
mentioning
confidence: 99%
“…The stratification process creates a potential for temperature differentials between deeper offshore and shallower near-shore subhabitats within a lake, as temperatures remain relatively constant in deep habitats, whereas shallower near-shore temperatures are strongly influenced by air temperatures (26). Monitoring in the boreal region (27,28) has shown that rising air temperature warms surface waters, accelerates the stratification process, and extends the duration of stratification; thus, air temperature is a primary determinant of lake thermal heterogeneity.…”
mentioning
confidence: 99%
“…The continuing absence of robust populations of three of the species in the lakes also indicates that conditions other than those we analyzed may be preventing their re-establishment. These factors could include absence of adequate food, competition, predation or climate change among others (Keller, 2007;Luek et al, 2010;Valois et al, 2010).…”
Section: Implications For Recoverymentioning
confidence: 99%
“…Future progress in the recovery of Daphnia species in Sudbury lakes will depend on the future trends of pH, cations and metals, and potentially on additional stressors such as climate change (Keller, 2007). The effects of predation, competition and the introduction of non-native species may also play a role (Keller, 2009;Luek et al, 2010), as well as the possibility of colonization by genetically adapted regional clones in the Sudbury area, as potentially better fitted for surviving and establishing successful colonies in the still metal contaminated lakes (Shaw et al, 2007).…”
Section: Implications For Recoverymentioning
confidence: 99%
“…Cyanobacteria are expected to benefit from the ever higher occurrence of summer heat waves (Jöhnk et al 2008, Paerl and. Milder winters and a shorter ice cover period (Magnuson et al 2000) provide opportunities for longer lasting and more pronounced diatom blooms, especially when mild winters lead to colder lake waters in spring (Keller 2007, Shatwell et al 2008. The brownification of boreal lakes, that has also been predicted as one possible outcome of climate change (Naden et al 2010), may benefit the growth of G. semen.…”
Section: Phytoplankton-related Issues In Lakesmentioning
confidence: 99%